2021
DOI: 10.4018/joeuc.290349
|View full text |Cite
|
Sign up to set email alerts
|

An End-to-End Bidirectional Authentication System for Pallet Pooling Management Through Blockchain Internet of Things (BIoT)

Abstract: Pallet pooling is regarded as a sustainable and cost-effective measure for the industry, but challenging to advocate due to weak data and pallet authentication.In order to establish trust between end-users and pallet pooling services, we propose an end-to-end, bidirectional authentication system for transmitted data and pallets based on blockchain and Internet-of-things (IoT) technologies. In addition, secure data authentication fosters the pallet authenticity in the whole supply chain network, which is achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Finally, 12% of the publications related to SCM and BCT are under the business/management/accounting field, followed by 5% under the environmental sciences area and 1% under agricultural and biological sciences. There are strong ties between BCT and IoT, and that is aligned with the recent research pointing out the future era of (BIoT) [37,38]…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Finally, 12% of the publications related to SCM and BCT are under the business/management/accounting field, followed by 5% under the environmental sciences area and 1% under agricultural and biological sciences. There are strong ties between BCT and IoT, and that is aligned with the recent research pointing out the future era of (BIoT) [37,38]…”
Section: Discussionsupporting
confidence: 62%
“…BCT, along with IoT, has a promising combination. For example, [37] proposed a pallet pooling system based on BCT and IoT (BIoT). They found that the suggested system positively impacts the overall quality of the pooling, increases end-user trust and satisfaction level, facilitates traceability, and minimizes errors.…”
mentioning
confidence: 99%
“…The literature suggests that algorithmic bias and unfairness in financial decision-making lead to discriminatory practices, inaccurate financial risk assessments, and legal and regulatory challenges (Balasubramaniam et al, 2020;Long et al, 2021). Biased decisions, as noted by Ghazwani et al (2022), result in tangible consequences that negatively affect the financial performance of institutions, such as investment and trading losses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that the suggested system positively impacts the overall quality of the pooling, increases end-user trust and satisfaction level, facilitates traceability, and minimizes errors. Moreover, this integration leverages cyber security by minimizing system vulnerabilities [53]. Metaverse and NFT are expected to elevate BCT applications across various industries from different spectrums.…”
Section: Future Research Opportunities: Next Generation Blockchainmentioning
confidence: 99%